Pengembangan E-LKPD Berbasis STEAM untuk Mendukung Kemampuan Numerasi Siswa Sekolah Dasar - Melly Nurdiyanzah; E.I. Pusta Siligar (Universitas Muhammadiyah Kotabumi, 2026)
Numeracy learning in elementary schools still faces various challenges, particularly students’ low ability to understand contextual problems and analyze data. This study aims to develop a STEAM-based e-LKPD that is valid, practical, and effective in improving students’ numeracy skills. The method used is Research and Development with the ADDIE model, which consists of analyze, design, development, implementation, and evaluation stages. The research subjects were fifth-grade elementary school students. The instruments included expert validation sheets, response questionnaires, and numeracy tests. The results showed that the e-LKPD achieved a very valid category from material, media, and language experts. In the implementation stage, the e-LKPD was categorized as very practical based on student and teacher responses. Furthermore, the effectiveness test indicated that the e-LKPD significantly improved students’ numeracy skills. The discussion revealed that the integration of STEAM in the e-LKPD created contextual, interactive, and meaningful learning experiences. Therefore, the STEAM-based e-LKPD can serve as an innovative solution to enhance numeracy skills in elementary school students.